An interface model to account for damage and plasticity at grain boundaries. Issue 1 (18th November 2019) - Rezaei, Shahed; Rezaei Mianroodi, Jaber; Brepols, Tim; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: Grain boundary (GB) characteristics play a major role in the understanding and prediction of polycrystalline behavior [1]. GB roles become more important when it comes to nanocrystalline metals and ceramics. To gain a deeper insight into the behavior of the grain boundary, molecular dynamics (MD) simulations are utilized. The Mode I, mode II and mixed mode loading behavior is investigated using different MD simulations. By adding the unloading path to the MD simulations it was possible to differentiate between different active mechanisms at the GB. An interface model is introduced based on our understanding from the atomistic simulation of the grain boundaries. When it comes to the grain boundary (GB) behavior, the current model is able to capture the competition between the intergranular fracture and the grain boundary sliding. The interface model is thermodynamically consistent and is able to capture the complex behavior of the GB under different loading conditions.